Surgical site infection after 769 Tibial Plateau Leveling Osteotomies - Husi, Benjamin; Overesch, Gudrun; Forterre, Franck; Rytz, Ulrich (Frontiers in Veterinary Science, 2023)
Objective: To report surgical site infections (SSI) after Tibial Plateau Leveling Osteotomy (TPLO), treatment course, associated risk factors, bacterial isolates and antimicrobial resistance. Study design: Retrospective clinical cohort study. Study population: 627 dogs and 769 TPLO procedures. Methods: Data from electronic medical records of dogs undergoing TPLO between 2005 and 2015 at a single institution have been retrospectively reviewed. A generalized mixed logistic regression was used to determine possible risk factors. The Chi-Square test of independence was used to examine the relationship between the isolation of multidrug-resistant (MDR) bacteria and the development of major infections undergoing additional surgical treatment. To assess the correlation between number of SSI and number MDR isolate per year, Pearson’s correlation coefficient was calculated. Results: The overall complication rate was 19.3% (n=149). SSI was most frequent with 8.5% (n=65). Major SSI occurred in 6.8% (n=52) TPLO (80.0% SSI). Staphylococcus (S.) pseudintermedius (n=37) and S. aureus (n=10) were most frequently isolated. Multidrug-resistant bacteria were identified in 2.7% (n=21) TPLO (32.3% SSI) but were not associated with major SSI (p= 0.426). There was a strong positive correlation between number of MDR isolates per year and number of SSI per year (r(9)=0.79, p=0.004). Factors associated with SSI were previous TPLO in the contralateral stifle (p=0.02, OR=2.01, 95% CI=1.11-3.64) and German Shepherd dogs (p=0.035, OR=4.41, 95% CI=1.11-17.54). The use of non-locking implants was found to be protective (p=0.02, OR=0.179, 95% CI=0.77-0.18). Clinical significance: Infection with multidrug-resistant bacteria is an emerging problem in veterinary practice and treatment is challenging. The incidence of major SSI was found to be high but was not associated with the isolation of MDR bacteria.